Current state of transfusion in traumatic brain injury and associated coagulopathy. (13th April 2019) - Stolla, Moritz; Zhang, Fangyi; Meyer, Michael R.; Zhang, Jianning; Dong, Jing‐Fei
ABSTRACT: Traumatic brain injury (TBI)‐induced coagulopathy has long been recognized as a significant risk for poor outcomes in patients with TBI, but its pathogenesis remains poorly understood. As a result, current treatment options for the condition are limited and ineffective. The lack of information is most significant for the impact of blood transfusions on patients with isolated TBI and in the absence of confounding influences from trauma to the body and limbs and the resultant hemorrhagic shock. Here we discuss recent progress in understanding the pathogenesis of TBI‐induced coagulopathy and the current state of blood transfusions for patients with TBI and associated coagulopathy.